2020
DOI: 10.3390/polym12112762
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Post-Curing Time on the Mechanical and Color Properties of Three-Dimensional Printed Crown and Bridge Materials

Abstract: Three-dimensional (3D) printing is increasingly being utilized in the dental field. After fabricating a prosthesis using a 3D printed resin, a post-curing process is required to improve its mechanical properties, but there has been insufficient research on the optimal post-curing conditions. We used various 3D printed crown and bridge materials in this study, and evaluated the changes in their properties according to post-curing time by evaluating the flexural strength, Weibull modulus, Vickers hardness, color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
138
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 141 publications
(151 citation statements)
references
References 45 publications
12
138
1
Order By: Relevance
“…In our study the flexural strength increased abruptly compared with the GS group after 15 min of postcuring. However, another previous study found no significant differences in flexural strength between their GS group and the group with 15 min of postcuring [25]. Moreover, none of the specimens in the present GS group fractured during the three-point bending test, which demonstrates the presence of flow plasticity.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations
“…In our study the flexural strength increased abruptly compared with the GS group after 15 min of postcuring. However, another previous study found no significant differences in flexural strength between their GS group and the group with 15 min of postcuring [25]. Moreover, none of the specimens in the present GS group fractured during the three-point bending test, which demonstrates the presence of flow plasticity.…”
Section: Discussioncontrasting
confidence: 65%
“…For measuring the unpolymerize rial, a drop of monomer resin was applied on a microscope slide an measurements were performed on the top surface of each disk, and scans was analyzed. The peak areas for aliphatic and aromatic C=C d and 1608 cm −1 , respectively, were analyzed [25,31]…”
Section: Degree Of Conversionmentioning
confidence: 99%
See 2 more Smart Citations
“…The post-curing method and time could affect the color of 3D printable materials. Kim et al evaluated the effect of post-curing time on the mechanical and color properties of 3D printable dental materials [ 51 ]. They reported that the color changed as the post-curing time increased and that this would be mainly due to the photoinitiators, as stated earlier in the manuscript.…”
Section: Discussionmentioning
confidence: 99%